Da “syn díkei” à lógica da Corporação – a superação da Tragödie im sittlichen na filosofia de hegel (Revista Eletrônica Estudos Hegelianos, 2016)
Resumo: Este trabalho se detém às relações da filosofia hegeliana com a literatura trágica greco-clássica, ao caráter análogo da natureza sistemática da narrativa trágica à cosmovisão da razão finita temporal moderna imersa num sistema de fatos que a excede e desafia. A tanto, analisa as interfaces do imaginário cultural da antiguidade e sua literatura, sobretudo com Ésquilo, com a filosofia de Hegel, quanto à relação da literatura trágica com a filosofia política compreendida em sua real-sistematicidade. Objetiva apreender as interfaces conceituais que habilitam conferir a unidade pretendida pela modernidade à cultura helênica ao incidir no pensamento de Hegel como a releitura da antiguidade greco-clássica à luz dos desafios legados pela filosofia kantiana. O itinerário da noção de liberdade que, da observância à lei divina, tanto adentra os assuntos humanos como a lei dos homens quanto se mantém dissociada da mesma no caráter transgressivo do herói trágico, tem na pretensão moderna do Eu os limites da eficiência particular, bem como a superação desta finitude pela subjetividade infinita articulada à racionalidade do Estado ético. Tal itinerário nega o estreito horizonte do subjetivismo na passagem da Sociedade civil-burguesa ao Estado e caracteriza o fracasso do paradigma consciencial pela superação do cidadão à tragédia burguesa. Palavras-chave: tragédia; liberdade; Hegel; burguês e cidadão. Abstract: The present work aims to examine the relations of the hegelian philosophy with classical greek tragic literature and also to examine the analogous character between the systematic nature of the tragic narrative and the world view (Weltanschauung) of the modern secular finite reason immersed in a system of facts that exceeds and defies it. In such a way, this work analyzes the interfaces of the antiquity´s cultural imaginary and the literature, over all in Aeschylus, and the relations that Hegel does between tragic literature and political philosophy understood in its real-sistematicity. This work also intends to apprehend the conceptual interfaces which able us to confer the unity intended by modernity to the Greek culture as it was analyzed in Hegel´s thought, that is, the well kown relecture of the classical greek antiquity in the light of the challenges left by kantian philosophy. The itinerary of the freedom notion that, by the observance of the divine law, goes through the human subjects as the men law as much as it remains dissociated from the same law in the transgressive character of the tragic hero. This itinerary has in the modern tradition of the Self the limits of the particular efficiency as much as the finitude is surpassed by infinite subjectivity articulated with rationality of the ethical State. And is yet the same itinerary that makes the negation of the narrow horizon of the subjectivism in the passing from the Civil-society to the State and characterizes the failure of the paradigm of conscience by the overcoming of the citizen on the bourgeois tragedy. Keywords: tragedy; freedom; Hegel; bourgeois and citizen.